Optimizing orbits for (e)LISA - Halloin, Hubert (Journal of physics. Conference series, 2017)
Earth and other planets gravitational fields induce perturbations of the (e)LISA constellation geometry (mostly flexing and Doppler frequency shifts). We present here a numerical optmization method minimizing these distrubances, subject to constraints (maximum distance to Earth and launch mass).